2004
DOI: 10.1081/jas-120033990
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Nitric Oxide Predicts Asthma Exacerbation

Abstract: The fraction of exhaled nitric oxide (FeNO) is elevated in asthmatics compared to normal subjects. Many studies have demonstrated that FeNO correlates with other markers of airway inflammation. The purpose of this study was to assess the clinical utility of routine monitoring of FeNO in determining its ability to predict future asthma exacerbations compared with other standard clinical measures of spirometry, peak flows, quality of life score, medication usage, and symptoms. A convenience sample of 22 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
2
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 22 publications
0
63
2
2
Order By: Relevance
“…23 With the appearance of cheaper portable handheld devices based on electrochemical sensing on the market, the possibility was contemplated to perform serial measurements to monitor disease activity and to steer asthma control, 24 especially because it was demonstrated that the increase of FeNO precedes the decrease in peak expiratory flow rates. 25 Another lucrative possibility is to titrate the optimal maintenance dose of inhaled steroids. 26 Taken together, these applications held the promise to use FeNO to guide asthma management.…”
Section: Nitric Oxidementioning
confidence: 99%
“…23 With the appearance of cheaper portable handheld devices based on electrochemical sensing on the market, the possibility was contemplated to perform serial measurements to monitor disease activity and to steer asthma control, 24 especially because it was demonstrated that the increase of FeNO precedes the decrease in peak expiratory flow rates. 25 Another lucrative possibility is to titrate the optimal maintenance dose of inhaled steroids. 26 Taken together, these applications held the promise to use FeNO to guide asthma management.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Measurement of exhaled NO has been suggested as helpful for monitoring airway inflammation in asthma, especially in cases of exacerbated asthma [9]. Another important aspect of asthma is that the matrix metalloproteinase-9 (MMP-9) level increases significantly in the bronchoalveolar lavage fluid (BALF), blood, and sputum of people with asthma [10].…”
Section: Introductionmentioning
confidence: 99%
“…The NO levels in the airways are increased in asthma animal models, as well as in patients with asthma (Kharitonov et al, 1995;Weicker et al, 2001). Measurement of exhaled NO has been suggested as being helpful in the monitoring of airway inflammation in asthma, especially in the case of exacerbated asthma (Harkins et al, 2004). However, the role of NO or NOS-mediated effects in the development of asthma exacerbation during viral infections remains controversial.…”
Section: Introductionmentioning
confidence: 99%